Smectic liquid crystal Schlieren texture in rapidly cooled poly(butylene naphthalate). (April 2018) - Ding, Qian; Jehnichen, Dieter; Göbel, Michael; Soccio, Michelina; Lotti, Nadia; Cavallo, Dario; Androsch, René
Graphical abstract: Highlights: Melt-crystallization of PBN was analyzed as a function of the crystallization conditions. Crystallization above 160 °C leads to formation of crystals and spherulites directly from the melt. Crystallization below 160 °C proceeds via intermediate formation of a smectic liquid crystalline (LC) phase. Cooling faster than 200–500 K/s suppresses crystal formation from the LC phase. The smectic LC phase exhibits a distinct Schlieren texture. Abstract: The morphology of partially crystalline/ordered poly(butylene naphthalate) (PBN) forming on cooling the melt has been analyzed by polarized-light optical microscopy (POM) and microfocus-beam X-ray diffraction (XRD). Crystallization at rather low supercooling of the melt, at temperatures higher than about 200 °C, leads to slow and irregular spherulitic growth of β′-crystals, with spherulites not showing a distinct Maltese cross in POM. At temperatures between approximately 200 and 160 °C, the melt partially converts directly to α-crystals, and the obtained spherulitic superstructure reveals an increasing nuclei density with decreasing crystallization temperature. At even lower temperature, a liquid crystalline (LC) phase develops. This mesophase may subsequently convert to α-crystals according to Ostwald's rule of stages. The transition of the LC-phase into α-crystals is suppressed at temperatures lower than about 120 °C or on cooling faster than about 200–500 K/s. X-ray analysis of PBN liquid crystals formed at well-defined cooling conditions in a fast scanning chip calorimeter revealed smectic periodicity while there is simultaneously observed a distinct Schlieren texture in POM.